Analisis Keterampilan Proses Sains Mahasiswa pada Praktikum Biologi Lingkungan Materi Bioindikator Pencemaran Air - Dian Putri Utami; Ima Aryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to understand skills in the science process in the environmental biology practicum on water pollution bioindicator material. This research method is a qualitative research method that involves descriptive analysis. The research results show that the order of indicator percentages from largest to smallest is, a) observations of 89%; b) classification of 87%; c) interpretation of 86%; d) communication of 83%; e) prediction of 78%; f) asking questions of 76%; g) hypothesizing of 69%; h) using tools and materials of 67%; i) applying the concept of 66%; j) planning an experiment of 63%. The conclusion of this research is that all PPP indicators appear in practicum. Keywords: Biology, KPS, Practicum